2009
DOI: 10.1111/j.1365-2133.2009.09116.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of calcipotriol plus betamethasone dipropionate scalp formulation compared with calcipotriol scalp solution in the treatment of scalp psoriasis: a randomized controlled trial

Abstract: A once-daily combination of calcipotriol plus betamethasone dipropionate was significantly more effective and better tolerated than twice-daily calcipotriol scalp solution in the treatment of scalp psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 20 publications
12
67
2
Order By: Relevance
“…The efficacy and safety of the combination of calcipotriol 50 mg/g, betamethasone dipropionate 0.5 mg/g, have been shown in previous studies (7)(8)(9)(10)(11)(12)(13)(14). The once-daily application of this combination in clinical studies on scalp psoriasis proved to be significantly superior to the individual components calcipotriol and betamethasone with respect to rapidity of effects and efficacy (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The efficacy and safety of the combination of calcipotriol 50 mg/g, betamethasone dipropionate 0.5 mg/g, have been shown in previous studies (7)(8)(9)(10)(11)(12)(13)(14). The once-daily application of this combination in clinical studies on scalp psoriasis proved to be significantly superior to the individual components calcipotriol and betamethasone with respect to rapidity of effects and efficacy (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 72%
“…This is a lipophilic gel formulation, particularly suitable for application to the scalp that combines the keratinocytes differentiation action of the vitamin D 3 analogues with the anti-inflammatory effect of steroids reducing the side-effect profile of the single topical agent. Previous studies showed the efficacy and safety of this combination in mild-to-moderate plaque-type psoriasis of body and scalp (7)(8)(9)(10)(11)(12)(13)(14). However, maintenance strategies after complete remission have been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a lipophilic gel containing betamethasone dipropionate plus calcipotriol was developed for once-daily application. In short-term studies, this two-compound gel is superior to monotherapy with betametasone propionate or calcipotriol (7)(8)(9). The longterm efficacy and safety of the two-compound gel was subsequently assessed in a 52-week, double-blind study of patients with moderate to severe scalp psoriasis (10).…”
Section: Long-term Efficacy and Safety Of Treatments For Scalp Psoriasismentioning
confidence: 99%
“…Randomized, placebo-controlled studies have demonstrated efficacy and safety for this indication. 28,29 …”
Section: Topical Retinoidsmentioning
confidence: 99%